Advanced machining technologies traditions and innovations - Grigoriev, S. N. (Materials science forum ;, 2015)
The issue is completed by articles of professors and scientists of MSTU STANKIN related to modern advanced technologies such as technologies of thin and thick resistant coatings for functional parts and cutting tools, diagnostics of technological processes and innovative technologies for material processing. The articles contain the description of the nowadays conditions and the last achievements in the University according to worldwide level. This issue is devoted to the 85th anniversary of MSTU STANKIN.